The relationship between strength, workability and acoustical properties of concrete block mixed with POFA as a replacement to cement / Abdul Wafi Razali - Razali, Abdul Wafi (2014)
The usage of agricultural waste in form of ashes as one of the constituent materials in concrete has been done through the years. Outnumber of research on this particular waste due to the existence of silica which can be classified into pozzolanic materials. Pozzolanic material is important to uphold the strength and durability of the concrete. This ash can easily be found at any palm oil mill in Malaysia. The objectives of this research are to evaluate the concrete compressive strength using POFA as cement replacement and to evaluate the performance of concrete blocks using POFA in term of sound insulation. This was done by correlating the relationship between the strength, water absorption and acoustic properties of concrete block using the same proportion of concrete mix. For this research, five different concrete mixture using ope. Generally, there are four different percentages of POFA replacement in concrete mixture which are 2.5%, 5%, 7.5% and 10% respectively. For compressive strength test and water absorption test, the concrete are tested on 7, 14 and 28 days. The same mixture also ,was used to conduct sound transmission loss test and sound absorption test. The concrete mixture was designed according to British standard with water cement ratio of 0.45. for compressive strength test and water absorption test, 9 cubes size 100mm x 100mm x 100mm were tested on 7, 14 and 28 days each. Meanwhile, for sound transmission loss test and sound absorption test, 20 concrete blocks size 240mm x 190mm x 100mm were tested on 7, 14 and 28 days for each test. Not to forget the slump test also was conducted for fresh concrete test. This research reveals the usage of POFA in concrete mixture can improve the compressive strength test and acoustical properties specifically for sound insulation. But the usage of POFA in concrete mixture strictly must not exceed 10% as it will decrease the performance of the concrete strength.